Helping themselves and helping others: how the passage of time influences why mothers with addictions take part in research - Crawford, Karen; Russell, Lynda; Graham, Sharon; Turner, Fiona (Frontiers in Psychiatry, 2023)
Introduction: Despite previous research suggesting women’s needs are less understood than men and gender-specific issues may be overlooked in Addiction Recovery Services, women with addiction issues are under-researched. The majority of women in treatment are mothers and a significant number have contact with child welfare services. The voices of these women are needed to shape and influence evidence-based treatment and service development. Aim: To examine reasons and rationale for participation in research in mothers with addiction issues and involvement with child welfare system. Method: Reflective thematic analysis was used on interview transcripts from two qualitative studies. Individual themes from each study were combined and analysed to develop themes covering both studies and at different timepoints in process of child welfare assessment or removal of child/ren. Results: Three themes were identified (1) Altruism; (2) Personal benefit; and (3) Empowerment. These mothers wanted to help with research. However, they also participated with the hope that this might facilitate the return of their children or help them to access support or services. A change over time was evident and in those further down the line from child removal, there was a stronger want for their voices to be heard in order to advocate for other women and create change in services.